Effect of Coffea canephora Bean Extract on Lead Acetate-Induced Rats - Fania Aulia Rahma; Moch. Ilham Riza Fahlefi; Maya Nurwartanti Yunita; Indaka Rachmach Choirunnisa; Farodina Azka Zhafira (Media Kedokteran Hewan, 2024)
Lead (Pb) is a non-essential heavy metal that is toxic and has no known uses. Most cases of poisoning in livestock are caused by lead poisoning. This study aims to determine the effect of Coffea canephora bean extract as an antioxidant on the heart histopathological features of white rats (Rattus norvegicus) induced by lead acetate. This study used 25 male Wistar rats aged between eight and ten weeks and weighing between 200 and 250 grams. The rats were divided into five treatment groups, namely negative control (C-), positive control (C+), treatment one (T1), treatment two (T2), and treatment three (T3).  The results suggested that the administration of 200 mg/kg BW, 400 mg/kg BW, or 800 mg/kg BW of Coffea canephora bean extract was not effective in improving the heart histopathological features, including cell degeneration, hemorrhage, and necrosis, of rats induced with lead acetate at a dose of 2 mg/kg BW.